Poželenje in prezir - Lipoglavšek, Manca (Amfiteater (Ljubljana), 2025)
The discourse on gender in the historical avant-garde movements, especially in Italian Futurism, is complex and internally contradictory. However, many female artists found an avenue for artistic engagement in the Futurist rebellion against traditional conservative values and sentimentalism. Female Futurists or female artists associated with the Futurist movement – such as Sibilla Aleramo, Mina Loy, Valentine de Saint-Point, Enif Robert, Rosa Rosa, Benedetta Cappa Mainetti, Magamal, Maria Ginanni, Maria Goretti, Gianinna Censi, Barbara, Regina, Marisa Mori, Rosetta Amadori Depero, and Luce and Elica Balla – created in their art a radically new conception of gender that explicitly challenged the prevailing standards of femininity. This article explores how the female Futurists addressed gender in their art, their role within the Futurist movement, and how female artists sought (or found) a path to emancipation through Futurist aesthetics and strategies
Keywords: avant-garde movements; avantgardna gibanja; feminism; feminizem; Futurism; futurizem; gender; spol; women of Futurism; ženske v futurizmu